Peningkatan Efisiensi Operasional Melalui Pendampingan Manajemen Keuangan Di Klinik Pratama Rawat Inap Vita Medika - Agoes Hari Edy Wibowo; Ridwan Hakiki (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Vita Medika Inpatient Primary Clinic is a first-level health facility that holds great potential in providing public health services. However, conventional and unintegrated financial management remains a major obstacle in measuring profitability and operational efficiency. This Community Service (PkM) activity aims to optimize the clinic's financial management through the restructuring of the recording system, training on digital-based financial report preparation, and unit cost analysis of services. The methods used include preliminary observation, focus group discussions (FGD), intensive training, and implementation assistance. The results of this activity indicate an 85% increase in administrative staff's understanding of operating financial software, the creation of a more accountable SOP for cash management, and the formulation of service tariff simulations based on a more precise unit cost calculation.